'They're my Contacts, not my Friends': Reconfiguring Affect and Aspirations Through Mobile Communication in Nigeria. Issue 2 (15th March 2018) - Gilbert, Juliet
ABSTRACT: In Calabar, Nigeria, young women envisage their futures to be full of possibilities. By contrast, their present realities often see them stuck in the house enduring long periods of waiting. Restricted by failing institutions, family and church pressures, and the fear of others' jealousy, young women find that there is no clear route to realising their aspirations. As they wait alone in the house, they constantly communicate with others on mobile phones and BlackBerries. This paper examines how young women in Calabar use mobile phones as a way of reconceptualising issues of trust, affect and intimacy. It argues that where they employ methods of concealment to chat with others – revealing neither their true identity nor personal details – mobile communication enables distance, becoming an invaluable means for creating new forms of sociality and future opportunities. Illuminating 'feminine cultures of waiting', this paper furthers recent analyses of youth, time and productivity.